Breakdown on LDPE film due to partial discharge in air gap and its correlation with electrical properties and surface degradation - Eka Putra Waldi; Yoshinobu Murakami; Masayuki Nagao (Universitas Ahmad Dahlan, 2019)
This paper describes the breakdown characteristic of the low density poly ethylene film caused by partial discharge in the air gap. The purpose of this paper is to clarify the effect number of discharge under repetition rectangular pulses with a needle-plane electrode system as a function of pulse frequency. The result performed, from 10 Hz up to 1000 Hz. From 10 Hz to 200 Hz, the pulse number up to breakdown did not change significantly with increasing the pulse frequency and the magnitude of partial discharge function of pulse number with varied frequency until breakdown were similar. By using both potential decay and surface degradation analysis function of number of pulse, the breakdown phenomena caused by partial discharge was shown to reveal a significant correlation between electrical properties and the transparency of its surface to change deposited on it by a partial discharge exposure.